Phytochemical Analysis And Molecular Docking Of Bioactive Constituents Present In Sesbania Grandiflora Leaves, To Cure Peptic Ulcers (Applied Biological Research, 2023)
Nonsteroidal anti-inflammatory drugs are major risk factor for peptic ulcers. Prostanoid E2 receptor 3 in parietal cell is a significant target for non-steroidal  anti-inflammatory drugs. Misoprostol is a standard medication used for its  treatment which has a lot of side effects. So people prefer herbs medicine to treat  this disease. The phytochemicals present in the leaves of Sesbania grandiflorahave the ability to heal peptic ulcers. In this study, the phytochemicals present  in its leaves were identified through gas chromatography and mass spectroscopy.  For this, the maceration method was used for phytochemical extraction with  ethanol used as extraction solvent. The chromatogram revealed 37 bioactive  compounds present in S. grandiflora extract. Molecular docking helps in drug  discovery by providing clues about the behaviour of small molecule in binding  sites of the target protein and fundamental biochemical process involved in the  formation of protein-ligand complex. β-amyrin, linolenic acid and L-α-terpineol  present in the leaves of S. grandiflora were considered for molecular docking  studies. All three components showed high binding affinity to prostaglandin 3  receptor E2, with β-amyrin having the highest affinity (-57.10 kcal mol-1). The  study revealed the binding affinity of bioactive components of S. grandiflora with  human prostaglandin E2 receptor 3, which may lead to the formulation of a  novel drug for peptic ulcers.
Keywords: Gas chromatography-mass spectrometry; gastric acid; molecular docking; prostaglandin E receptor 3; Sesbania grandiflora